Infrastructure development as a driver of trade liberalization in the belt and road initiative african countries: A case study from Kenya - Ibouanga, Kone; Mve, Symphorien Engone; Mikala, Hermine Balouki (Asian Journal of Empirical Research, 2024)
Several studies have been carried out on the determinants of international trade. However, little is known about the relationship between infrastructure development and international trade in sub-Saharan African (SSA) countries in general and in Kenya in particular. This article examines the effect of infrastructure development on international trade. Thus, it concerns the analysis of Kenya’s economy during the period 1980-2021.The Autoregressive and Distributed Lags (ARDL) method is employed as estimation technique and different types of infrastructures such as rail lines, paved roads and access to electricity have been highlighted. Moreover, two indicators of international trade named external trade rate and Squalli and Wilson index were employed. The results revealed that access to electricity, paved roads as well as rail lines improve Kenya's external trade rate in the long run. However, no significant relationship was found in the short run. Moreover, the robostness of the results was confirmed with the Squalli and Wilson index. Therefore, Kenya’s goverment must pursue its national infrastructure development program with the support of other development partners by emphasizing the intensification of electricity, the construction of roads and railway lines. To achieve its infrastructure goals Kenya needs to develop the second phase of the Country Strategy Document.